THE READABILITY OF BILINGUAL COMIC “WOW OF CINDERELLA” TRANSLATION TECHNIQUES - Kiki Simanullang; Klara Sipayung; Kammer Tuahman Sipayung; Harpen Silitonga (Sean Institute, 2022)
This research entitled The Readability of Bilingual Comic “Wow of Cinderella” Translation Techniques. This research aimed to describe the translation techniques based on Molina and Albir’s theory and to know the readability of translation used in bilingual comic “Wow of Cinderella”. This research used descriptive qualitative method. Data of this research were sentences in bilingual comic both English and Indonesian. The raters of this research are student of Senior High School, student of University and an English teacher. They are asking to read the bilingual comic then do the questionnaire. In analyzing the data, the writer used comparison method to compare between the SL and TL that were analyzed. The result of this research showed that target text used eighteen translation techniques. They are Adaptation 3%, Amplification 4%, Borrowing 2%, Calque 2%, Compensation 7%, Description 5%, Discursive Creation 1%, Established Equivalence 2%, Generalization 2%, Linguistics Amplification 5%, Linguistics Compression 4%, Literal Translation 34%, Modulation 9%, Particularization 1%, Reduction 5%, Substitution 1%, Transposition 9%, Variation 4%. And the percentage of the readability also shown that Readability 80%, less readability 14,67% and unreadability 5,33%. From the percentage, the researcher concludes that the translation techniques used in this bilingual comic is readability.